Turkey's International Responsibility for Internationally Wrongful Acts Committed by the Ottoman Empire - Dumberry, Patrick (Revue générale de droit, 2012)
This paper examines the legal consequences of the commission by the Ottoman Empire of internationally wrongful acts, including acts of genocide, against the Armenian population during World War I. Specifically, the present paper examines the following question: can the modern State of Turkey (which was only officially proclaimed in 1923) be held responsible, under international law, for internationally wrongful acts committed by the Ottoman Empire before its disintegration? This paper first briefly examines whether Turkey should be considered, under international law, as the "continuing" State of the Ottoman Empire or whether it should instead be deemed as a "new" State, We will show that Turkey is, in legal terms, "identical" to the Ottoman Empire and is therefore "continuing" the international legal personality of the Empire. This paper will then focus on the legal consequences arising from this conclusion of continuity. Our analysis of past case law and State practice shows that both in the context of secession and of cession of territory, the continuing State continues to be held responsible for its own internationally wrongful acts committed before the date of succession. Accordingly, Turkey should be held responsible for all internationally wrongful acts committed by the Ottoman Empire.